Thiopurine pharmacogenomics and pregnancy in inflammatory bowel disease - Andoh, Akira; Kawahara, Masahiro; Imai, Takayuki; Tatsumi, Goichi; Inatomi, Osamu; Kakuta, Yoichi (Journal of gastroenterology, 2021)
The thiopurine drugs azathioprine and 6-mercaptopurine are widely used for the maintenance of clinical remission in steroid-dependent inflammatory bowel disease (IBD). Thiopurines are recommended to be continued throughout pregnancy in IBD patients, but conclusive safety data in pregnant patients remain still insufficient. On the other hand, a strong association between a genetic variant of nucleoside diphosphate-linked moiety X-type motif 15 (NUDT15 p.Arg139Cys) and thiopurine-induced myelotoxicity has been identified. Pharmacokinetic studies have revealed that thiopurine metabolism is altered in pregnant IBD patients and suggested that the fetus may be exposed to the active-thiopurine metabolite, 6-thioguaninetriphosphate, in the uterus. A recent study using knock-in mice harboring the p.Arg138Cys mutation which corresponds to human p.Arg139Cys showed that oral administration of 6-MP at clinical dose induces a severe toxic effect on the fetus harboring the homozygous or heterozygous risk allele. This suggests that NUDT15 genotyping may be required in both women with IBD who are planning pregnancy (or pregnant) and their partner to avoid adverse outcomes for their infant. The risk to the fetus due to maternal thiopurine use is minimal but there are some concerns that are yet to be clarified. In particular, a pharmacogenomic approach to the fetus is considered necessary.